2021
DOI: 10.3389/fpls.2021.650432
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, Chlorophyll Fluorescence, and Yield of Peanut in Response to Biochar Application

Abstract: The effect of biochar application on photosynthetic traits and yield in peanut (Arachis hypogaea L.) is not well understood. A 2-year field experiment was conducted in Northwest Liaoning, China to evaluate the effect of biochar application [0, 10, 20, and 40 t ha−1 (B0, B10, B20, and B40)] on leaf gas exchange parameters, chlorophyll fluorescence parameters, and yield of peanut. B10 improved photochemical quenching at flowering and pod set and reduced non-photochemical quenching at pod set, relative to B0. B10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 65 publications
(72 reference statements)
3
10
0
Order By: Relevance
“…This result may be due to rain that occurred the day before soil sampling, thus soils were at a water‐saturated state. The application of biochar was beneficial to increase total nitrogen and phosphorus content in leaves, in agreement with other studies reporting increased content of such nutrients in leaves following biochar application (Wang et al, 2021). Leaf nitrogen content is important for photosynthesis and structural development of plants, including the synthesis of proteins, amino acids, nucleic acids, enzymes, chlorophyll, alkaloids and other important substances (Mao et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…This result may be due to rain that occurred the day before soil sampling, thus soils were at a water‐saturated state. The application of biochar was beneficial to increase total nitrogen and phosphorus content in leaves, in agreement with other studies reporting increased content of such nutrients in leaves following biochar application (Wang et al, 2021). Leaf nitrogen content is important for photosynthesis and structural development of plants, including the synthesis of proteins, amino acids, nucleic acids, enzymes, chlorophyll, alkaloids and other important substances (Mao et al, 2012).…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown that net photosynthesis rate ( P n ) and transpiration rate ( T r ) increased by 19 and 40% in the biochar treatments, respectively, compared to control ( Zulfiqar et al, 2021 ). Biochar significantly increased net photosynthetic rate, transpiration rate, stomatal conductance, and water use efficiency during the plant growth period, relative to control ( Wang et al, 2021 ). Chlorophyll fluorescence parameters can effectively reflect the absorption, utilization, and transformation of light energy.…”
Section: Discussionmentioning
confidence: 90%
“…Y (II) represents the actual photosynthetic quantum yield of PSII, which can reflect the current actual light energy conversion efficiency of photosynthetic organs ( Baker, 2008 ). Research has shown that biochar has great potential in improving chlorophyll fluorescence ( Wang et al, 2021 ). That’s probably because biochar has the effect of increasing the chlorophyll content of leaves ( Feng et al, 2021 ), which can ensure the synthesis of various enzymes and electron transporters in the process of carbon assimilation in photosynthesis, thereby improving the function of leaf photosynthesis ( Hou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al . (2021) reported that applications of 10 and 20 t/ha BC (of unspecified source) improved the photosynthetic electron transfer rate and the proportion of open PSII reaction centres in leaves of peanut ( Arachis hypogaea L.) plants and reduced energy dissipation in the form of heat, allowing the full use of the light energy absorbed by leaves for photosynthesis. These authors also indicated that BC applications increased N uptake from the soil and improved the leaf chlorophyll content, which stimulated the synthesis of various enzymes and electron transporters that enhance the photosynthetic function in leaves.…”
Section: Discussionmentioning
confidence: 99%